Active energy ray-curable antifogging coating composition, cured product, and laminate

By using a radical polymerizable compound with a specific structure and a water-soluble surfactant in the anti-fog resin composition, the problem of the reduction of anti-fog properties after long-term use of the existing anti-fog resin composition is solved, and an anti-fog coating film with high wear resistance, exudation resistance and moisture and heat resistance is achieved.

CN119768476APending Publication Date: 2025-04-04DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060922.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-08-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The surfactant exudes after long-term use of the existing anti-fog resin composition, resulting in a decrease in antifog properties and deterioration of the coating appearance, and poor wear resistance and antifog properties after repeated cleaning.

Method used

An active energy ray-curing anti-fog coating composition containing a radical polymerizable compound (A) having a specific structure and a water-soluble surfactant (B) is used to form a cured coating film with excellent anti-fog properties, wear resistance, exudation resistance and moisture and heat resistance by combining the specific structure of the radical polymerizable compound and the water-soluble surfactant.

Benefits of technology

It has achieved long-term and continuous anti-fog resistance, excellent wear resistance, leakage resistance, adhesion and moisture and heat resistance, and is suitable for automobiles, displays and residential interior decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768476A_ABST
    Figure CN119768476A_ABST
Patent Text Reader

Abstract

Provided are an active energy ray-curable antifogging coating composition, a cured product, and a laminate which are capable of forming a cured coating film having long-term antifogging properties and excellent wear resistance, bleed-out resistance, adhesion, and wet heat resistance. The present invention relates to: an active energy ray-curable antifogging coating composition containing a radical polymerizable compound (A) having a structure selected from among formulae (1) to (3) and a water-soluble surfactant (B); a cured product of the active energy ray-curable antifogging coating composition; the laminate is characterized by having a coating film containing a cured product. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an active energy ray-curable anti-fog coating composition, a cured product and a laminate. Background Art

[0002] In recent years, high anti-fogging properties are required to prevent fogging for automobile headlights, virtual reality (VR) displays, etc. Here, the so-called fogging is a phenomenon caused by diffuse reflection of light caused by water droplets attached to the surface. As anti-fogging methods for preventing such fogging, generally known methods include a method of reducing the contact angle of water, a method of absorbing water attached to the surface, a method of giving water repellency to the surface to repel water, etc. Among them, the method of reducing the contact angle of water is often used because it is simple and has good anti-fogging performance.

[0003] As a method for reducing the contact angle of water, attempts have been made to form an anti-fog coating by coating an anti-fog resin composition on the surface of glass or plastic as a substrate. Conventional anti-fog resin compositions are generally a mixture of a hydrophilic polymer and a surfactant, and include a thermosetting composition using a catalyst or isocyanate, and an active energy ray-curable composition based on a compound having a polymerizable reaction group and a polymerization initiator.

[0004] However, conventional anti-fogging resin compositions have been subjected to surfactant exudation due to long-term use, resulting in reduced anti-fogging properties or deterioration of the coating appearance, and poor abrasion resistance or anti-fogging properties after repeated surface cleaning. Therefore, a durable anti-fogging resin composition that can withstand long-term use and cleaning procedures during dirt attachment is required.

[0005] Therefore, as an anti-fogging resin composition having excellent anti-fogging properties, durability of anti-fogging properties, and abrasion resistance, there is known an ultraviolet curable anti-fogging composition which does not use a surfactant and contains ethoxylated bisphenol A di(meth)acrylate having an average addition mole number of ethylene oxide in the range of 10 to 30, a hydrophilic monofunctional monomer, a polar diluent solvent, and a photopolymerization initiator (for example, see Patent Document 1).

[0006] In addition, Patent Document 2 discloses a composition having excellent primary antifogging properties immediately after coating and secondary antifogging properties after durability tests such as water resistance tests, which comprises a hydroxyl-containing (meth)acrylate compound having a specific epoxy equivalent, a specific amount of a nonionic antifogging agent, and a mixing accelerator containing a water-containing unsaturated group.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-239832

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-210396 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] However, the inventions described in Patent Documents 1 and 2 do not investigate the bleed-out resistance after the moisture and heat resistance test, and therefore it cannot be said that the inventions described in Patent Documents 1 and 2 relate to anti-fogging compositions having sufficient durability.

[0013] The present invention has been made in view of the above problems and provides an active energy ray-curable anti-fog coating composition, a cured product and a laminate having long-lasting anti-fogging properties and excellent abrasion resistance, bleed resistance, adhesion and moisture-heat resistance.

[0014] Solutions for solving problems

[0015] As a result of studies, the present inventors have found that an active energy ray-curable anti-fog coating composition comprising a radically polymerizable compound (A) having a specific structure and a water-soluble surfactant (B) can solve the above-mentioned problems, thereby completing the present invention.

[0016] That is, the present invention provides the following inventions.

[0017] [1] An active energy ray-curable anti-fog coating composition comprising a radical polymerizable compound (A) having any structure of the following formulae (1) to (3) and a water-soluble surfactant (B),

[0018]

[0019] (In formula (1), n ​​is an integer of 0 to 10, and (2+n) Xs are independently a (meth)acryloyl group modified with ethylene oxide [CH2=CR-CO(OC2H4)y-; R represents a hydrogen atom or a methyl group, and y represents the number of modifications with ethylene oxide], a (meth)acryloyl group [CH2=CR-CO-; R represents a hydrogen atom or a methyl group], or a hydrogen atom, and at least one of the plurality of Xs represents a (meth)acryloyl group modified with ethylene oxide; and the average number of modifications with ethylene oxide per (meth)acryloyl group in the compound is 1 to 5)

[0020]

[0021] (In formula (2), n is an integer of 0 to 4, and (4+2n) Xs are independently a (meth)acryloyl group modified with ethylene oxide [CH2=CR-CO(OC2H4)y-; R represents a hydrogen atom or a methyl group, and y represents the number of modifications based on ethylene oxide], a (meth)acryloyl group [CH2=CR-CO-; R represents a hydrogen atom or a methyl group], or a hydrogen atom, and at least one of the plurality of Xs represents a (meth)acryloyl group modified with ethylene oxide; in addition, the average number of modifications of ethylene oxide per (meth)acryloyl group in the compound is 1 to 5)

[0022]

[0023] (In formula (3), n is an integer from 0 to 3, and (3+n) Xs are independently a (meth)acryloyl group modified with ethylene oxide [CH2=CR-CO(OC2H4)y-; R represents a hydrogen atom or a methyl group, and y represents the number of modifications based on ethylene oxide], a (meth)acryloyl group [CH2=CR-CO-; R represents a hydrogen atom or a methyl group], or a hydrogen atom, and at least one of the multiple Xs represents a (meth)acryloyl group modified with ethylene oxide; in addition, the average number of modifications of ethylene oxide per (meth)acryloyl group in the compound is 1 to 5).

[0024] [2] The active energy ray-curable anti-fog coating composition according to [1], further comprising a compound (C) having a carboxyl group and a (meth)acryloyl group and a compound (D) having an alkoxysilyl group and a (meth)acryloyl group.

[0025] [3] The active energy ray-curable anti-fog coating composition according to [1] or [2], further comprising a polyfunctional (meth)acrylate (E) that is not modified with ethylene oxide.

[0026] [4] The active energy ray-curable anti-fog coating composition according to any one of [1] to [3], comprising a polyfunctional (meth)acrylate (F) having a polyethylene glycol structure.

[0027] [5] A cured product obtained by irradiating the active energy ray-curable resin composition according to any one of [1] to [4] with active energy rays.

[0028] [6] A laminate having a cured coating film on at least one surface of a plastic substrate, wherein the cured coating film comprises the cured product according to [5].

[0029] [7] A laminate having a cured coating film on at least one surface of a glass substrate, wherein the cured coating film comprises the cured product according to [5].

[0030] Effects of the Invention

[0031] The active energy ray-curable anti-fog coating composition of the present invention can form a cured coating film and a cured product having long-lasting anti-fog properties and excellent abrasion resistance, oozing resistance, adhesion, and moisture and heat resistance. The cured coating film can withstand conditions in a high temperature and high humidity environment and conditions with many opportunities for contact with people and objects, and exhibits excellent anti-fog properties. Therefore, the active energy ray-curable anti-fog coating composition of the present invention can be suitably used as an anti-fog property-imparting coating agent in automotive applications, display applications, and residential interior decoration. DETAILED DESCRIPTION

[0032] In this specification, the compound represented by formula (1) is referred to as "compound (1)", and the compounds represented by other formulae are referred to similarly. In addition, "acrylate" and "methacrylate" are collectively referred to as "(meth)acrylate", and "methacryloyl" and "acryloyl" are collectively referred to as "(meth)acryloyl".

[0033] The radical polymerizable compound (A) is referred to as "component (A)", and the other compounds (B) to (C) are referred to similarly.

[0034] <Active energy ray-curable anti-fog coating composition>

[0035] The active energy ray-curable anti-fog coating composition of the present invention (hereinafter sometimes simply referred to as “composition”) contains a radical polymerizable compound (A) and a water-soluble surfactant (B) as essential components.

[0036] As the evaluation method of the present invention, the initial anti-fogging property and repeated anti-fogging property of the coating film formed by curing the composition were tested. The case where these test results are excellent is regarded as having anti-fogging property and anti-fogging persistence. Furthermore, the wear resistance, substrate adhesion before and after the moisture and heat resistance test, and the exudation resistance after the moisture and heat resistance test were tested. The case where these test results are excellent is regarded as having excellent wear resistance, exudation resistance, adhesion and moisture and heat resistance.

[0037] [Radical polymerizable compound (A)]

[0038] The radical polymerizable compound (A) is a compound having any of the structures of the above formulae (1) to (3), and is a component that imparts antifogging properties to the cured coating film of the present invention.

[0039] For the compound of component (A), the more the number of (meth)acryloyl groups in one molecule, the better the wear resistance and oozing resistance of the cured coating of the composition. If the number of (meth)acryloyl groups in one molecule is smaller, the adhesion of the cured coating to the substrate, the anti-fogging property and the anti-fogging persistence are improved. Therefore, from the viewpoint of balancing the wear resistance, oozing resistance, substrate adhesion, anti-fogging property and anti-fogging persistence of the cured coating, the number of (meth)acryloyl groups in one molecule is preferably in the range of 1 to 8, and more preferably in the range of 3 to 6.

[0040] In addition, for the compound of component (A), the average number of ethylene oxide modifications per (meth)acryloyl group (hereinafter referred to as "EO average modification number") is in the range of 1 to 5, more preferably in the range of 1 to 3, and particularly preferably in the range of 1 to 2. The smaller the EO average modification number, the better the abrasion resistance, bleed resistance and substrate adhesion of the cured coating film.

[0041] Specific examples of the compound represented by formula (1) include ethoxylated glycerol tri(meth)acrylate having an average EO modification number of 1 to 5 and ethoxylated 1,2,3,4-butanetetrol tetra(meth)acrylate.

[0042] Specific examples of the compound represented by formula (2) include ethoxylated pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, etc., each having an average number of EO modifications of 1 to 5.

[0043] Specific examples of the compound represented by formula (3) include ethoxylated trimethylolpropane tri(meth)acrylate and ethoxylated ditrimethylolpropane tetra(meth)acrylate having an average number of EO modifications of 1 to 5.

[0044] As the component (A), the compounds (1) to (3) may be used alone or in combination of two or more.

[0045] Among them, as the component (A), it is preferred to use at least the compound (2) or the compound (3), and more preferably ethoxylated dipentaerythritol hexa(meth)acrylate having an average EO modification number of 1 to 3 or ethoxylated trimethylolpropane triacrylate having an average EO modification number of 1 to 3.

[0046] The preferred lower limit of the content of the component (A) in the composition of the present invention is 1%, 2%, 3%, 5%, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% relative to the total amount of the radical polymerizable compound contained in the composition. The preferred upper limit of the content is 100%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25% relative to the total amount of the radical polymerizable compound contained in the composition.

[0047] As described later, the composition of the present invention may contain a radical polymerizable compound in addition to the component (A), and may be used in combination according to the required performance of the cured coating film, such as abrasion resistance, oozing resistance, substrate adhesion, anti-fogging property, and anti-fogging persistence. Therefore, the most suitable combination of the upper limit and the lower limit varies depending on the combination of the radical polymerizable compound other than the component (A), and will be described later.

[0048] [Water-soluble surfactant (B)]

[0049] The water-soluble surfactant (B) is a component that improves the anti-fog property and anti-fog persistence of the cured coating. In addition, the so-called water solubility here is defined as no turbidity or separation is visually confirmed when the surfactant is mixed with water at a mass ratio of 1:1 at 25°C. If the surfactant is water-soluble, the anti-fog property and anti-fog persistence of the cured coating become good. In the case of a water-insoluble surfactant, the anti-fog property and anti-fog persistence of the cured coating are reduced.

[0050] The component (B) may be selected from anionic surfactants, cationic surfactants, and nonionic surfactants, and may be a single component or a combination of a plurality of components.

[0051] As the anionic surfactant, any known anionic surfactant can be used as long as it is water-soluble, and examples thereof include fatty acid salts such as sodium oleate and potassium oleate; higher alcohol sulfates such as sodium lauryl sulfate and ammonium lauryl sulfate; alkylbenzenesulfonates and alkylnaphthalenesulfonates such as sodium dodecylbenzenesulfonate and sodium alkylnaphthalenesulfonate; naphthalenesulfonic acid dialkylphosphate ester salts, naphthalenesulfonic acid formaldehyde condensation products, dialkylsulfosuccinates, dialkylphosphate ester salts, polyoxyethylene sulfates such as sodium polyoxyethylene alkylphenyl ether sulfate; fluorine-containing anionic surfactants such as perfluoroalkyl carboxylates, perfluoroalkylsulfonates, and perfluoroalkylphosphates, etc. Among them, dioctylsulfosuccinate is more preferred from the viewpoint of the persistence of anti-fogging properties and anti-bleeding properties.

[0052] As the cationic surfactant, any known one can be used as long as it is water-soluble, and examples thereof include amine salts such as ethanolamines, laurylamine acetate, triethanolamine monoformate, and stearylamide ethyl diethylamine acetate; alkyl trimethyl ammonium salts such as lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, and cetyl trimethyl ammonium chloride; dialkyl dimethyl ammonium salts such as dilauryl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, and stearyl dimethyl benzyl ammonium chloride; fluorine-containing cationic surfactants such as perfluoroalkyl trimethyl ammonium salts, etc. Among them, quaternary ammonium salts having 10 to 36 carbon atoms are preferred, quaternary ammonium salts having 10 to 24 carbon atoms are more preferred, and alkyl trimethyl ammonium salts having 10 to 20 carbon atoms are further preferred.

[0053] As the nonionic surfactant, any conventionally known surfactant can be used as long as it is water-soluble, and examples thereof include: polyoxyethylene higher alcohol ethers such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenol and polyoxyethylene nonylphenol; polyoxyethylene acyl esters such as polyoxyethylene glycol monostearate; polyoxyethylene sorbitan fatty acid esters such as polypropylene glycol ethylene oxide adducts, polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; phosphate esters such as alkyl phosphate esters and polyoxyethylene alkyl ether phosphate esters; sugar esters, cellulose ethers; fluorine-containing nonionic surfactants such as perfluoroalkylamine oxides, perfluoroalkylethylene oxide adducts, oligomers having a perfluoroalkyl group and a hydrophilic group, oligomers having a perfluoroalkyl group and a lipophilic group, and oligomers having a perfluoroalkyl group and a hydrophilic group and a lipophilic group. Among them, polyoxyalkylene alkyl ethers having 8 to 20 carbon atoms and polyoxyethylene styrenated phenyl ethers are preferred, polyoxyalkylene alkyl ethers having 8 to 20 carbon atoms are preferred, and polyoxyalkylene alkyl ethers having 8 to 20 carbon atoms in the hydrophobic group are more preferred. Polyoxyalkylene alkyl ethers having 10 to 16 carbon atoms in the hydrophobic group are more preferred, and polyoxyalkylene alkyl ethers containing ethylene oxide groups having an HLB value of 6 to 18 and 10 to 16 carbon atoms in the hydrophobic group are further preferred.

[0054] The component (B) is not particularly limited, but among the above, it is preferred to contain at least an anionic surfactant, and more preferably to use both an anionic surfactant and a cationic surfactant, from the viewpoint of the sustainability of the anti-fogging property and the anti-bleeding property.

[0055] When anionic surfactants and cationic surfactants are used in combination, the blending ratio [(anion) / (cation)] is preferably in the range of 100 / 1 to 5 / 1, and particularly preferably in the range of 33 / 1 to 10 / 1. By setting it in these ranges, the anti-fogging property is sustained and the anti-bleeding property is improved.

[0056] From the viewpoint of long-term maintenance of anti-fogging properties and improvement of anti-bleeding properties, the content of component (B) is preferably in the range of 0.5 to 10.0% by mass, more preferably in the range of 0.75 to 7.5% by mass, and particularly preferably in the range of 1.0 to 5.0% by mass, relative to the total amount of the radically polymerizable compounds contained in the composition.

[0057] The composition of the present invention may also contain a radical polymerizable compound other than component (A). Examples of radical polymerizable compounds other than component (A) include a compound (C) having a carboxyl group and a (meth)acryloyl group, a compound (D) having an alkoxysilyl group and a (meth)acryloyl group, a multifunctional (meth)acrylate (E) not modified by ethylene oxide, and a multifunctional (meth)acrylate (F) having a polyethylene glycol structure. Component (E) is a compound that does not belong to component (C) and component (D), and component (F) is a compound that does not belong to component (A), component (C), and component (D).

[0058] [Compound (C) Having a Carboxyl Group and a (Meth) Acryloyl Group]

[0059] The compound (C) having a carboxyl group and a (meth)acryloyl group is a component that improves the adhesion to a substrate, in particular, the adhesion to a glass substrate. However, the component (C) does not contain an alkoxysilyl group in the molecule.

[0060] Examples of the component (C) include (meth)acrylic acid, crotonic acid, o-vinylbenzoic acid, m-vinylbenzoic acid, p-vinylbenzoic acid, α-halogenated alkyl, alkoxy, halogen, nitro or cyano substituents of (meth)acrylic acid, β-carboxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, ω-carboxypolycaprolactone mono(meth)acrylate, 2-(meth)acryloyloxyethyl hydrogenated phthalate, 2-(meth)acryloyloxypropyl hydrogenated phthalate, 2-(meth)acryloyloxy unsaturated monocarboxylic acids such as 2-(meth)acryloyloxypropyl tetrahydrophthalate; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, citraconic acid, alkenyl succinic acid, alkadienyl succinic acid, and endic acid; half ester compounds obtained from the unsaturated dicarboxylic acids and monohydric alcohols; reaction products of alcohols having a (meth)acryloyl group and acid anhydrides such as tetrahydrophthalic anhydride, phthalic anhydride, hexahydrophthalic anhydride, succinic anhydride, and maleic anhydride, etc.

[0061] Examples of alcohols having a (meth)acryloyl group include, for monofunctional acrylates, hydroxyalkyl methacrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, and cyclohexanedimethanol mono(meth)acrylate; and for multifunctional acrylates, trimethylolpropane di(meth)acrylate, pentaerythritol, Tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol ethylene oxide modified penta(meth)acrylate, dipentaerythritol propylene oxide modified penta(meth)acrylate, dipentaerythritol caprolactone modified penta(meth)acrylate, glycerol acrylate methacrylate, glycerol dimethacrylate, methacrylate 2-hydroxy-3-acryloylpropyl, the reaction product of epoxy-containing compound and carboxyl (meth)acrylate, hydroxyl-containing polyol polyacrylate. In addition, as a commercially available product, for example, ARONIX (registered trademark) M510, M520 (made by Toagosei Co., Ltd.) etc. can also be used. These compounds can be used alone or in combination of two or more.

[0062] Among them, as the component (C), it is more preferable to use a reaction product of (meth)acrylic acid, an acid anhydride and an alcohol having a (meth)acryloyl group, and particularly preferably 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl hexahydrophthalate.

[0063] The preferred lower limit of the content of the component (C) in the composition of the present invention is 0.5%, 1%, 2%, 3%, 5%, 7%, 10%, 15% relative to the total amount of the radical polymerizable compound contained in the composition. The preferred upper limit of the content is 30%, 25%, 20%, 15% relative to the total amount of the radical polymerizable compound contained in the composition.

[0064] As described later, the composition of the present invention may also contain radical polymerizable compounds other than components (A) and (C), and can be used in combination according to the required performance of the cured coating film, such as abrasion resistance, oozing resistance, substrate adhesion, anti-fogging property, and anti-fogging persistence. Therefore, the most suitable combination of the upper limit and the lower limit varies depending on the combination of radical polymerizable compounds other than components (A) and (C), and is therefore described later.

[0065] [Compound (D) Having an Alkoxysilyl Group and a (Meth)acryloyl Group]

[0066] The compound (D) having an alkoxysilyl group and a (meth)acryloyl group is a component that improves adhesion to a substrate, particularly to a glass substrate. However, the component (D) does not contain a carboxyl group in the molecule.

[0067] Examples of the alkoxysilyl group in the component (D) include silyl groups substituted with 1 to 3, preferably 2 or 3, alkyl groups having 1 to 4 carbon atoms, preferably 1 to 2 carbon atoms, such as trimethoxysilyl, triethoxysilyl, and dimethoxysilyl. Among these, trimethoxysilyl and triethoxysilyl are preferred from the viewpoint of substrate adhesion, and trimethoxysilyl is particularly preferred.

[0068] As component (D), there is no particular limitation as long as the compound has the above-mentioned alkoxysilyl group and (meth) acryloyl group in the structure of the compound, and examples thereof include: a structure formed by introducing an alkoxysilyl group into the allyl group of allyl acrylate or allyl methacrylate by hydrosilylation, etc.; as a structure derived therefrom, examples thereof include: acrylate (3-trimethoxysilylpropyl) ester, acrylate (3-triethoxysilylpropyl) ester, methacrylate (3-trimethoxysilylpropyl) ester, methacrylate (3-triethoxysilylpropyl) ester, methacrylate (3-trimethoxysilylpropyl) ester, methacrylate (3-triethoxysilylpropyl) ester, etc. As commercial products, trade names "KBM510", "KBM5103", "KBM503", "KBM5803" (all manufactured by Shin-Etsu Chemical Co., Ltd.) and the like can be used. These compounds can be used alone or in combination of two or more.

[0069] Among them, 3-(meth)acryloxypropyltrimethoxysilane is particularly preferred from the viewpoint of improving substrate adhesion and heat resistance. These compounds may be used alone or in combination of two or more.

[0070] The preferred lower limit of the content of the component (D) in the composition of the present invention is 0.5%, 1%, 2%, 3%, 5%, 7%, 10%, 15% relative to the total amount of the radical polymerizable compound contained in the composition. The preferred upper limit of the content is 30%, 25%, 20%, 15% relative to the total amount of the radical polymerizable compound contained in the composition.

[0071] As described later, the composition of the present invention may also contain radical polymerizable compounds other than components (A) and (D), and may be used in combination according to the required performance of the cured coating film, such as abrasion resistance, oozing resistance, substrate adhesion, anti-fogging properties, and anti-fogging persistence. Therefore, the most suitable combination of the upper and lower limits of the content varies depending on the combination of radical polymerizable compounds other than components (A) and (D), and will be described later.

[0072] [Polyfunctional (meth)acrylate not modified with ethylene oxide (E)]

[0073] The polyfunctional (meth)acrylate (E) not modified with ethylene oxide is a component that improves the adhesion to the substrate. The component (E) is a compound that does not contain a carboxyl group and / or an alkoxysilyl group.

[0074] Examples of the non-ethylene oxide-modified polyfunctional (meth)acrylate (E) include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-modified glycerol tri(meth)acrylate, propylene oxide-modified glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, hydroxypivalic acid-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, and dipentaerythritol tetra(meth)acrylate. , dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, a urethane (meth)acrylate compound formed by reacting an isocyanate compound with an alcohol compound, a polyester (meth)acrylate compound synthesized by a condensation reaction of a polyol with (meth)acrylic acid and a multifunctional carboxylic acid, an epoxy (meth)acrylate compound synthesized by an addition reaction of a bisphenol-type epoxy resin or a novolac-type epoxy resin with (meth)acrylic acid, and the like. As commercially available products, dipentaerythritol penta(meth)acrylate (various products under the trade name "ARONIX (registered trademark)" manufactured by Toagosei Co., Ltd. (M-400, M-403, M-404, M-405, M-406, etc.)), pentaerythritol tri(meth)acrylate (various products under the trade name "ARONIX (registered trademark)" manufactured by Toagosei Co., Ltd. (M-306, M-305, M-303, M-452, M-450, etc.)) can be used. These compounds may be used alone or in combination of two or more.

[0075] Among them, from the viewpoint of improving substrate adhesion, abrasion resistance, and moist heat resistance, a compound having three or more (meth)acryloyl groups in the molecule is preferred, and dipentaerythritol hexa(meth)acrylate is particularly preferred.

[0076] The preferred lower limit of the content of the component (E) in the composition of the present invention is 7%, 9%, 10%, 18%, 27%, 30%, and 50% relative to the total amount of the radical polymerizable compound contained in the composition. The preferred upper limit of the content is 95%, 90%, 70%, 66.5%, 63%, 50%, 49%, 27%, and 25% relative to the total amount of the radical polymerizable compound contained in the composition.

[0077] As described later, the composition of the present invention may also contain radical polymerizable compounds other than components (A) and (E), and may be used in combination according to the required performance of the cured coating film, such as abrasion resistance, oozing resistance, substrate adhesion, anti-fogging properties, and anti-fogging persistence. Therefore, the most suitable combination of the upper limit and lower limit of the content varies depending on the combination of radical polymerizable compounds other than components (A) and (E), and will be described later.

[0078] [Multifunctional (meth)acrylate having a polyethylene glycol structure (F)]

[0079] The polyfunctional (meth)acrylate (F) having a polyethylene glycol structure imparts hydrophilicity and improves the rigidity of the cured coating film, thereby improving the anti-fogging durability and anti-bleeding properties. Component (F) is a compound that does not belong to component (A), component (C) and component (D).

[0080] Various known substances can be used as the component (F), and the raw materials and the production method are not limited. For example, it can be a product containing polyethylene glycol, an isocyanate compound and a (meth)acrylate compound having a hydroxyl group as essential reaction raw materials, or a product containing polyethylene glycol and a (meth)acrylate compound having a carboxyl group as essential reaction raw materials.

[0081] As the polyethylene glycol, commercially available products may be used, and examples thereof include "PEG" series (PEG-200, PEG-400, PEG-600, PEG-1000, PEG-2000, PEG-4000, etc.) manufactured by Sanyo Chemical Industries, Ltd., and the like.

[0082] Examples of the isocyanate compound include aromatic isocyanates such as diphenylmethane diisocyanate and toluene diisocyanate; aliphatic isocyanates such as 1,6-hexamethylene diisocyanate, 1,4-butane diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; and alicyclic isocyanate compounds such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, norbornane diisocyanate, hydrogenated xylene diisocyanate, 2-methyl-1,3-diisocyanatocyclohexane, and 2-methyl-1,5-diisocyanatocyclohexane. Alternatively, dimers and trimers (isocyanurates, biuret, allophanates, etc.) of these isocyanate compounds may be used. Among them, aliphatic isocyanates are more preferred from the viewpoint of the persistence of anti-fogging properties and the resistance to oozing out after a wet heat resistance test, and hexamethylene diisocyanate or its isocyanurate is particularly preferred.

[0083] Examples of the (meth)acrylate compound having a hydroxyl group include dipentaerythritol penta(meth)acrylate (commercially available products include various products under the trade name "ARONIX (registered trademark)" manufactured by Toagosei Co., Ltd. (M-400, M-403, M-404, M-405, M-406, etc.)), pentaerythritol tri(meth)acrylate (commercially available products include various products under the trade name "ARONIX (registered trademark)" manufactured by Toagosei Co., Ltd. (M-306, M-305, M-303, M-452, M-450, etc.)), 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxyethyl (meth)acrylate, -hydroxypropyl ester, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy mono(meth)acrylate (for example, the trade name "PLACCEL (registered trademark) FA-2D" manufactured by Daicel, etc.), polycarbonate-modified hydroxy mono(meth)acrylate (for example, the trade name "HEMAC (registered trademark)" manufactured by Daicel, etc.), polyethylene glycol- or polypropylene glycol-modified hydroxy mono(meth)acrylate (for example, the trade name "Blemmer (registered trademark) AE-200", "Blemmer (registered trademark) AP-400" manufactured by NOF Corporation, etc.), etc.

[0084] Examples of the compound having a carboxyl group include (meth)acrylic acid, crotonic acid, o-vinylbenzoic acid, m-vinylbenzoic acid, p-vinylbenzoic acid, α-halogenated alkyl, alkoxy, halogen, nitro or cyano substituents of (meth)acrylic acid, β-carboxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, ω-carboxypolycaprolactone mono(meth)acrylate, 2-(meth)acryloyloxyethyl hydrogenated phthalate, 2-(meth)acryloyloxypropyl hydrogenated phthalate. unsaturated monocarboxylic acids such as esters, 2-(meth)acryloxypropyl hexahydrophthalate, and 2-(meth)acryloxypropyl tetrahydrophthalate; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, citraconic acid, alkenyl succinic acid, dienyl succinic acid, and endic acid; half ester compounds obtained from the unsaturated dicarboxylic acids and monohydric alcohols; reaction products of alcohols having a (meth)acryloyl group with acid anhydrides such as tetrahydrophthalic anhydride, phthalic anhydride, hexahydrophthalic anhydride, succinic anhydride, and maleic anhydride, etc.

[0085] The component (F) may be used alone or in combination of two or more compounds. From the viewpoint of the persistence of anti-fogging properties and the resistance to exudation, the component (F) is preferably a compound containing 4 or more (meth)acryloyl groups in the molecule, and more preferably 6 or more. From the same viewpoint, the number average molecular weight of the polyethylene glycol used as the raw material of the component (F) is preferably 200 to 4000, preferably 400 to 4000, and particularly preferably 600 to 4000.

[0086] The preferred lower limit of the content of the component (F) in the composition of the present invention is 10%, 20%, 30%, 40%, or 50% relative to the total amount of the radical polymerizable compound contained in the composition, and the preferred upper limit of the content is 90%, 80%, 70%, 60%, or 50% relative to the total amount of the radical polymerizable compound contained in the composition.

[0087] As described later, the composition of the present invention may also contain radical polymerizable compounds other than components (A) and (F), and may be used in combination according to the required performance of the cured coating film, such as abrasion resistance, oozing resistance, substrate adhesion, anti-fogging properties, and anti-fogging persistence. Therefore, the most suitable combination of the upper limit and lower limit of the content varies depending on the combination of radical polymerizable compounds other than components (A) and (F), and will be described later.

[0088] <Combination of Radically Polymerizable Compounds>

[0089] As described above, the composition of the present invention has component (A) as an essential component with respect to the free radical polymerizable compound, and may also use any one or more of components (C) to (F) as arbitrary components in combination according to the required performance of the cured coating film, such as abrasion resistance, bleed resistance, substrate adhesion, anti-fog property and anti-fog persistence. Examples of the combination of the components are shown below.

[0090] [Examples containing component (A)]

[0091] Even when the composition contains the component (A) as a radical polymerizable compound and does not contain the components (C) to (F), a composition capable of forming a cured coating film having abrasion resistance, bleed-out resistance, substrate adhesion, antifogging properties, and antifogging sustainability can be obtained.

[0092] When components (C) to (F) are not contained, the content of component (A) relative to the total amount of the radical polymerizable compound contained in the composition is preferably in the range of 50 to 100% by mass, particularly preferably in the range of 70 to 100% by mass, and particularly preferably in the range of 90 to 100% by mass. By setting it to these ranges, a composition can be formed that has excellent abrasion resistance, oozing resistance, substrate adhesion, anti-fogging properties, and anti-fogging persistence.

[0093] When more excellent substrate adhesion is required, it is preferred to further contain the components (C) and (D). The improvement of substrate adhesion to a glass substrate by adding the components (C) and (D) is particularly significant.

[0094] [Examples containing the components (A), (C) and (D)]

[0095] An example in which the components (A), (C) and (D) are contained as radical polymerizable compounds and the components (E) and (F) are not contained will be described below.

[0096] By using the components (C) and (D) in combination in addition to the component (A), the adhesion to substrates before and after the heat resistance test is improved. The adhesion to all known substrates is improved, and the adhesion to glass substrates is particularly improved.

[0097] When the composition contains components (A), (C) and (D), the content of component (A) is preferably in the range of 50 to 99% by mass, more preferably in the range of 60 to 95% by mass, and particularly preferably in the range of 70 to 90% by mass, relative to the total amount of the radical polymerizable compound contained in the composition. In addition, the total content of components (C) and (D) is preferably in the range of 1 to 50% by mass, more preferably in the range of 5 to 40% by mass, and particularly preferably in the range of 10 to 30% by mass, relative to the total amount of the radical polymerizable compound contained in the composition.

[0098] By setting the total content of the components (A), (C) and (D) to be within these ranges, anti-fogging properties, anti-fogging durability, anti-bleeding properties and abrasion resistance are improved, and substrate adhesion after a moisture and heat resistance test is further improved.

[0099] The blending ratio of component (D) to component (C) [(C) / (D)] is preferably in the range of 90 / 10 to 10 / 90, more preferably in the range of 80 / 20 to 20 / 80, and particularly preferably in the range of 75 / 25 to 25 / 75. By setting it in these ranges, the substrate adhesion after the moisture and heat resistance test is improved.

[0100] When further improvement of the bleed-out resistance and the abrasion resistance is required, it is preferred to further contain the component (E).

[0101] [Examples containing the components (A), (C), (D) and (E)]

[0102] An example in which the components (A), (C), (D), and (E) are contained as radical polymerizable compounds and the component (F) is not contained will be described below.

[0103] By containing the component (E) in addition to the component (C) and the component (D), the adhesion to the substrate is improved, and the bleed-out resistance and the abrasion resistance are further improved.

[0104] When all components (C) to (E) are contained, the content of component (A) is preferably in the range of 2 to 70% by mass, more preferably in the range of 3.5 to 65% by mass, and particularly preferably in the range of 5 to 50% by mass, relative to the total amount of the radical polymerizable compound contained in the composition. In addition, the total content of components (C) to (E) is preferably in the range of 30 to 98% by mass, more preferably in the range of 35 to 97% by mass, and particularly preferably in the range of 50 to 95% by mass, relative to the total amount of the radical polymerizable compound contained in the composition.

[0105] By setting the content of the component (A) and the total content of the components (C) to (E) within these ranges, excellent antifogging properties and antifogging durability are achieved, and substrate adhesion after a moisture and heat resistance test, anti-bleeding properties, and abrasion resistance are further improved.

[0106] In addition, the blending ratio [(C) / (D) / (E)] of component (C), component (D), and component (E) is preferably in the range of 40 / 40 / 20 to 15 / 15 / 70, more preferably in the range of 30 / 30 / 40 to 16 / 16 / 68, and particularly preferably in the range of 25 / 25 / 50 to 20 / 20 / 80. By setting it to these ranges, the substrate adhesion after the moisture and heat resistance test, the anti-bleeding property, and the abrasion resistance are improved.

[0107] When further improvement of the anti-fogging durability is required, it is preferred to further contain the component (F).

[0108] [Examples containing the components (A), (C), (D), (E) and (F)]

[0109] Examples of the radical polymerizable compound containing the component (A), the component (C), the component (D), the component (E), and the component (F) are described below.

[0110] By containing the component (F) in addition to the components (C) to (E), the substrate adhesion, bleed-out resistance, and abrasion resistance after the moisture and heat resistance test are improved, and the anti-fogging durability is further improved.

[0111] When all of components (C) to (F) are contained, the content of component (A) is preferably in the range of 1 to 56 mass %, more preferably 2 to 49 mass %, and particularly preferably 3 to 42 mass % relative to the total amount of the radical polymerizable compound contained in the composition.

[0112] The total content of the components (C) and (D) is preferably 5 to 35% by mass, more preferably 8 to 32% by mass, and particularly preferably 10 to 30% by mass, based on the total amount of the radical polymerizable compound contained in the composition.

[0113] The total content of the components (E) and (F) is preferably in the range of 28 to 89% by mass, more preferably 35 to 88% by mass, and particularly preferably 42 to 87% by mass, based on the total amount of the radical polymerizable compound contained in the composition.

[0114] By setting the content of component (A), the total content of component (C) and component (D), and the total content of component (E) and component (F) to these ranges, excellent anti-fogging properties, substrate adhesion after a moisture and heat resistance test, anti-bleeding properties, and abrasion resistance are achieved, and the anti-fogging sustainability is further improved.

[0115] When all components (C) to (F) are contained, the blending ratio of component (F) to component (E) [(E) / (F)] is preferably in the range of 10 / 90 to 75 / 25, more preferably in the range of 20 / 80 to 55 / 45, and particularly preferably in the range of 25 / 75 to 41 / 59. By setting it in these ranges, the substrate adhesion, anti-bleeding and abrasion resistance after the moisture and heat resistance test are improved.

[0116] From the viewpoint of improving adhesion to a glass substrate, it is particularly preferred to contain components (C) and (D). However, in the case of a substrate other than glass, such as a resin substrate, even if components (C) and (D) are not contained, a cured coating film having excellent anti-fogging properties, anti-fogging persistence, substrate adhesion, abrasion resistance, and oozing resistance can be formed.

[0117] [Examples containing the component (A) and the component (E)]

[0118] An example in which the components (A) and (E) are contained as radical polymerizable compounds and the components (C), (D) and (F) are not contained will be described below.

[0119] By containing the component (E) in addition to the component (A), the anti-fogging property, the anti-fogging persistence, the substrate adhesion, the abrasion resistance and the anti-bleeding property are further improved.

[0120] When the component (E) is contained and the component (C), the component (D) and the component (F) are not contained, the content of the component (A) is preferably in the range of 5 to 90% by mass, more preferably in the range of 10 to 70% by mass, and particularly preferably in the range of 30 to 50% by mass, relative to the total amount of the radical polymerizable compound contained in the composition. In addition, the content of the component (E) is preferably in the range of 10 to 95% by mass, more preferably in the range of 30 to 90% by mass, and particularly preferably in the range of 50 to 70% by mass, relative to the total amount of the radical polymerizable compound contained in the composition.

[0121] By setting the contents of the component (A) and the component (E) within these ranges, the antifogging property, the antifogging persistence, the substrate adhesion, the abrasion resistance, and the anti-bleeding property are further improved.

[0122] When further excellent anti-bleeding property and anti-fogging durability are required, it is preferred to further contain the component (F).

[0123] [Examples containing the components (A), (E) and (F)]

[0124] An example in which the components (A), (E), and (F) are contained as radical polymerizable compounds and the components (C) and (D) are not contained will be described below.

[0125] By containing the components (E) and (F) in addition to the component (A), the anti-bleeding property and the anti-fogging durability are further improved.

[0126] When the components (E) and (F) are contained and the components (C) and (D) are not contained, the content of the component (A) is preferably in the range of 1 to 63% by mass, more preferably in the range of 2 to 56% by mass, and particularly preferably in the range of 3 to 49% by mass. In addition, the total content of the components (E) and (F) is preferably in the range of 30 to 99% by mass, more preferably in the range of 44 to 98% by mass, and particularly preferably in the range of 50 to 97% by mass, relative to the total amount of the radical polymerizable compound contained in the composition.

[0127] By setting the content of the component (A) and the total content of the component (E) and the component (F) to be within these ranges, the anti-bleeding property and the anti-fogging durability are further improved.

[0128] The blending ratio of the component (F) to the component (E) [(E) / (F)] is preferably in the range of 9 / 91 to 75 / 25, more preferably in the range of 18 / 82 to 55 / 45, and particularly preferably in the range of 25 / 75 to 38 / 72. By setting it in these ranges, the anti-bleeding property and the anti-fogging durability are improved.

[0129] Furthermore, the active energy ray-curable anti-fog coating composition of the present invention may also contain a photopolymerization initiator.

[0130] [Photopolymerization initiator]

[0131] Examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, thioxanthone and thioxanthone derivatives, 2,2′-dimethoxy-1,2-diphenylethane-1-one, diphenyl(2,4,6-trimethoxybenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one.

[0132] The above-mentioned photopolymerization initiators may be used alone or in combination of two or more.

[0133] The content of the photopolymerization initiator is preferably 0.01 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and particularly preferably 1 to 5 parts by mass relative to the total amount of the radical polymerizable compound contained in the composition. If the content of the photopolymerization initiator is 0.1 parts by mass or more, the curing reaction proceeds appropriately, and a cured coating film with high hardness can be obtained, which is preferred. On the other hand, if the content of the photopolymerization initiator is 10 parts by mass or less, yellowing is not likely to occur, and a cured product with high transparency can be obtained, which is preferred.

[0134] The composition of the present invention may also contain a solvent. By containing a solvent, the viscosity of the composition can be adjusted.

[0135] [Solvent]

[0136] Examples of the aforementioned solvent include: alcohol solvents such as methanol, ethanol, 1-propanol, tert-butanol, and diacetone alcohol; alcohol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, carbitol, and cellosolve; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, and butyl acetate; aromatic solvents such as toluene, xylene, and butylhydroxytoluene; and the like.

[0137] The above-mentioned solvents may be used alone or in combination of two or more.

[0138] The content of the aforementioned solvent is preferably 0 to 300 parts by mass, more preferably 0 to 100 parts by mass, relative to 100 parts by mass of the solid content of the aforementioned active energy ray-curable anti-fog coating composition. If the content of the aforementioned solvent is 300 parts by mass or less, it is easy to control the film thickness, so it is preferred. In addition, if the content of the solvent is more than 10 parts by mass, various coating methods such as spray coating and flow coating can be adopted, so it is preferred.

[0139] Furthermore, the active energy ray-curable anti-fog coating composition of the present invention may contain other additives as necessary.

[0140] [Other ingredients]

[0141] Representative examples of other components include free radical polymerizable compounds, various resins, fillers, ultraviolet absorbers, and leveling agents. In addition, the composition may further contain inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, catalysts, surfactants other than component (B), stabilizers, flow regulators, coupling agents, dyes, rheology control agents, antioxidants, plasticizers, and the like.

[0142] As the radical polymerizable compound, a (meth)acrylate compound other than components (A) and (C) to (F) and a compound having a double bond such as a vinyl group may be added. Specifically, examples thereof include a monofunctional (meth)acrylate compound α having no carboxyl group and / or alkoxysilyl group, and a compound β having all of an alkoxysilyl group, a carboxyl group, and a (meth)acryloyl group in the molecule.

[0143] Examples of the monofunctional (meth)acrylate compound α having no carboxyl group and / or alkoxysilyl group include acryloylmorpholine, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy (meth)acrylate (e.g., trade name "PLACCEL" manufactured by Daicel Co., Ltd.), a reaction product of phthalic anhydride or succinic anhydride and hydroxyalkyl (meth)acrylate, a mono(meth)acrylate of a polyester diol obtained from succinic acid and ethylene glycol, a mono(meth)acrylate of a polyester diol obtained from succinic acid and propylene glycol, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, acrylamide, dimethylacrylamide, diethylacrylamide, amino (meth)acrylate, (meth)acrylate containing an ionic group such as a sulfonic acid group or a quaternary ammonium salt, and (meth)acrylic acid adducts of various epoxy esters.

[0144] Examples of the compound β having all of an alkoxysilyl group, a carboxyl group, and a (meth)acryloyl group in the molecule include a reaction product obtained by a dehydration condensation reaction of a compound having a trialkoxysilyl group and succinic anhydride (such as X12-967C manufactured by Shin-Etsu Chemical Co., Ltd.) and a compound having a trialkoxysilyl group and a (meth)acryloyl group (such as KBM-503 and KBM-5103 manufactured by Shin-Etsu Chemical Co., Ltd.), and a reaction product obtained by modifying the hydroxyl group of epoxy acrylate with an acid anhydride and then partially reacting a (meth)acrylate having a glycidyl group.

[0145] In addition, liquid organic polymers may be used for viscosity adjustment. The so-called liquid organic polymers are liquid organic polymers that do not directly participate in the curing reaction, and examples thereof include: modified polymers containing carboxyl groups (FLOWLEN G-900, NC-500: Kyoei Chemical Industry Co., Ltd.), acrylic polymers (FLOWLEN WK-20: manufactured by Kyoei Chemical Industry Co., Ltd.), amine salts of special modified phosphate esters (HIPLAAD (registered trademark) ED-251: manufactured by Kusumoto Chemicals Co., Ltd.), and modified acrylic block copolymers (DISPERBYK (registered trademark) 2000; manufactured by BYK-Chemie Co., Ltd.).

[0146] As various resins, thermosetting resins and thermoplastic resins can be used.

[0147] So-called thermosetting resin is a resin having a property of being substantially insoluble and infusible when being cured by means such as heating or radiation, catalysts, etc. As a specific example, so-called thermosetting resin is a resin having a property of being substantially insoluble and infusible when being cured by means such as heating or radiation, catalysts, etc. As a specific example, it can be listed as: phenolic resin, urea resin, melamine resin, benzoguanamine (benzoguanamine) resin, alkyd resin, unsaturated polyester resin, vinyl ester resin, diallyl terephthalate resin, epoxy resin, silicone resin, carbamate resin, furan resin, ketone resin, xylene resin, thermosetting polyimide resin, benzoxazole resin, active ester resin, aniline resin, cyanate resin, styrene-maleic anhydride (SMA) resin, etc. These thermosetting resins can be used 1 or used in combination of 2 or more.

[0148] The so-called thermoplastic resin refers to a resin that can be melt-molded by heating. Specific examples thereof include polyethylene resin, polypropylene resin, polystyrene resin, rubber-modified polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, polymethyl methacrylate resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyethylene terephthalate resin, ethylene-vinyl alcohol resin, cellulose acetate resin, ionomer resin, polyacrylonitrile resin, polyamide resin, polyacetal resin, polybutylene terephthalate resin, polylactic acid resin, polyphenylene ether resin, modified polyphenylene ether resin, polycarbonate resin, polysulfone resin, polyphenylene sulfide resin, polyetherimide resin, polyethersulfone resin, polyarylate resin, thermoplastic polyimide resin, polyamideimide resin, polyetheretherketone resin, polyketone resin, liquid crystal polyester resin, fluororesin, syndiotactic polystyrene resin, cyclic polyolefin resin, etc. These thermoplastic resins can be used alone or in combination of two or more.

[0149] As the filler, for example, silica can be blended for the purpose of improving hard coating properties.

[0150] Silica is not limited, and known silica particles such as powdered silica and colloidal silica can be used. Examples of commercially available powdered silica particles include: the trade name "AEROSIL (registered trademark)" series (50, 200, etc.) manufactured by NIPPON AEROSIL, the trade name "Sildex" series (H31, H32, H51, H52, H121, H122, etc.) manufactured by AGC, the trade name "E220A" or "E220" manufactured by Tosoh Silica, the trade name "SYLYSIA (registered trademark) 470" manufactured by FUJI SILYSIA CHEMICAL, the trade name "SGflake" manufactured by Nippon Sheet Glass, etc.

[0151] Examples of commercially available colloidal silica include “Methanol Silica Sol,” “IPA-ST,” “MEK-ST,” “PGM-ST,” “NBA-ST,” “XBA-ST,” “DMAC-ST,” “ST-UP,” “ST-OUP,” “ST-20,” “ST-40,” “ST-C,” “ST-N,” “ST-O,” “ST-50,” and “ST-OL,” all manufactured by Nissan Chemical Industries, Ltd.

[0152] Reactive silica may also be used as the silica. Examples of reactive silica include reactive compound-modified silica. Examples of reactive compounds include reactive silane coupling agents having a hydrophobic group, compounds having a (meth)acryloyl group, compounds having a maleimide group, and compounds having a glycidyl group.

[0153] Examples of commercially available powdered silica modified with a compound having a (meth)acryloyl group include: "AEROSIL (registered trademark) RM50" and "AEROSIL (registered trademark) R711" manufactured by NIPPON AEROSIL Co., Ltd.; examples of commercially available colloidal silica modified with a compound having a (meth)acryloyl group include: "MIBK-SD", "MIBK-SD-L", "MIBK-AC-2140Z", "MEK-AC-2140Z" manufactured by Nissan Chemical Industries, Ltd. In addition, examples of reactive silica include: silica modified with a glycidyl group such as 3-glycidoxypropyltrimethoxysilane and then subjected to an addition reaction with acrylic acid, and silica modified with a compound having a hydroxyl group and a (meth)acryloyl group subjected to a urethanization reaction with 3-isocyanatepropyltriethoxysilane.

[0154] The shape of the silica particles is not particularly limited, and spherical, hollow, porous, rod-shaped, plate-shaped, fibrous or irregular shapes can be used. For example, commercially available hollow silica particles can be made under the trade name "SiliNax (registered trademark)" manufactured by Nippon Iron & Steel Co., Ltd.

[0155] The primary particle size is preferably in the range of 5 to 200 nm. When the primary particle size is 5 nm or more, the inorganic fine particles in the composition are sufficiently dispersed, and when the primary particle size is 200 nm or less, sufficient strength of the cured product can be maintained.

[0156] The content of silica is preferably 3 to 60% by mass based on 100% by mass of the composition.

[0157] Examples of fillers other than silica include inorganic fillers and organic fillers. The shape of the filler is not limited, and examples thereof include granular, plate-like, and fibrous fillers.

[0158] Fillers with excellent heat resistance include aluminum oxide, magnesium oxide, titanium oxide, zirconium oxide, etc.; those with excellent thermal conductivity include boron nitride, aluminum nitride, aluminum oxide, titanium oxide, magnesium oxide, zinc oxide, silicon oxide, etc.; those with excellent electrical conductivity include metal fillers and / or metal-coated fillers using metal single substances or alloys (such as iron, copper, magnesium, aluminum, gold, silver, platinum, zinc, manganese, stainless steel, etc.); those with excellent barrier properties include minerals such as mica, clay, kaolinite, talc, zeolite, wollastonite, montmorillonite, potassium titanate, magnesium sulfate, sepiolite, xonotlite, boron nitride, etc. The following are some examples of the materials used in the invention: aluminum oxide, calcium carbonate, titanium oxide, barium sulfate, zinc oxide, and magnesium hydroxide; those with high refractive index include barium titanate, zirconium oxide, and titanium oxide; those showing photocatalytic properties include titanium, cerium, zinc, copper, aluminum, tin, indium, phosphorus, carbon, sulfur, tellurium, nickel, iron, cobalt, silver, molybdenum, strontium, chromium, barium, and lead, photocatalytic metals, complexes of the aforementioned metals, and oxides thereof; those with excellent wear resistance include metals such as aluminum oxide, zirconium oxide, and magnesium oxide, as well as complexes and oxides thereof; those with excellent conductivity include metals such as silver and copper, tin oxide, and indium oxide; and those with excellent ultraviolet shielding properties include titanium oxide and zinc oxide.

[0159] These inorganic particles can be selected according to the application, and can be used alone or in combination. In addition, the inorganic particles have various properties other than those listed above, so they can be selected according to the application.

[0160] In addition to inorganic fibers such as carbon fiber, glass fiber, boron fiber, alumina fiber, and silicon carbide fiber, inorganic fibers such as carbon fiber, activated carbon fiber, graphite fiber, glass fiber, tungsten carbide fiber, silicon carbide fiber, ceramic fiber, alumina fiber, natural fiber, mineral fibers such as basalt, boron fiber, boron nitride fiber, boron carbide fiber, and metal fiber can also be cited. Examples of the above-mentioned metal fibers include aluminum fiber, copper fiber, brass fiber, stainless steel fiber, and steel fiber.

[0161] Examples of organic fibers include synthetic fibers made of resin materials such as polybenzazole, aramid, PBO (polyparaphenylene benzoxazole), polyphenylene sulfide, polyester, acrylic, polyamide, polyolefin, polyvinyl alcohol, and polyarylate; natural fibers such as cellulose, pulp, cotton, wool, and silk; and regenerated fibers such as protein, polypeptide, and alginic acid.

[0162] The content of the filler is preferably 0 to 60% by mass in 100% by mass of the composition.

[0163] Examples of the ultraviolet absorber include benzophenone-based, benzotriazole-based, benzotriazine-based, cyclic imide ester-based, cyanoacrylate-based, and polymer-type ultraviolet absorbers.

[0164] The composition of the present invention may be used in combination with a light stabilizer for the purpose of improving light resistance. Examples of the light stabilizer include hindered amine stabilizers (HALS) and the like.

[0165] Various surface modifiers may be added to the composition of the present invention for the purpose of improving leveling during coating, improving the slip of the cured film to improve scratch resistance, etc. As the surface modifier, various additives that modify the surface properties and are commercially available under the names of surface adjusters, leveling agents, slip imparting agents, antifouling imparting agents, etc. may be used. Among these, silicone-based surface modifiers and fluorine-based surface modifiers are suitable.

[0166] Specifically, silicone polymers and oligomers having silicone chains and polyalkylene oxide chains, silicone polymers and oligomers having silicone chains and polyester chains, fluorine polymers and oligomers having perfluoroalkyl and polyalkylene oxide chains, fluorine polymers and oligomers having perfluoroalkyl ether chains and polyalkylene oxide chains, etc. It is sufficient to use one or more of these. For the purpose of improving the durability of sliding properties, those containing (meth) acryloyl groups in the molecule may also be used. Specific examples of the surface modifier include EBECRYL (registered trademark) 350 (manufactured by DAICEL-ALLNEX), BYK-333 (manufactured by BYK-Chemie Japan), BYK-377 (manufactured by BYK-Chemie Japan), BYK-378 (manufactured by BYK-Chemie Japan), BYK-UV3500 (manufactured by BYK-Chemie Japan), BYK-UV3505 (manufactured by BYK-Chemie Japan), BYK-UV3576 (manufactured by BYK-Chemie Japan), BYK-UV3577 (manufactured by BYK-Chemie Japan), BYK-UV3578 (manufactured by BYK-Chemie Japan), BYK-UV3579 (manufactured by BYK-Chemie Japan), BYK-UV3580 (manufactured by BYK-Chemie Japan), BYK-UV3581 (manufactured by BYK-Chemie Japan), BYK-UV3582 (manufactured by BYK-Chemie Japan), BYK-UV3583 (manufactured by BYK-Chemie Japan), BYK-UV3584 (manufactured by BYK-Chemie Japan), BYK-UV3585 (manufactured by BYK-Chemie Japan), BYK-UV3586 (manufactured by BYK-Chemie Japan), BYK-UV3587 (manufactured by BYK-Chemie Japan), BYK-UV3588 (manufactured by BYK-Chemie Japan), BYK-UV3589 (manufactured by BYK-Chemie Japan), BYK-UV3590 (manufactured by BYK-Chemie Japan), BYK-UV3591 (manufactured by BYK Japan Co., Ltd.), MEGAFAC (registered trademark) RS-75 (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-76-E (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-72-K (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-76-NS (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-90 (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-91 (manufactured by DIC Corporation), MEGAFAC (registered trademark) RS-55 (manufactured by DIC Corporation), OPTOOL (registered trademark) DAC-HP (manufactured by Daikin Corporation), ZX-058-A (manufactured by T&K TOKA), ZX-201 (manufactured by T&K TOKA), ZX-202 (manufactured by T&K TOKA), ZX-212 (manufactured by T&K TOKA), ZX-214-A (manufactured by T&K TOKA), X-22-164AS (Shin-Etsu Chemical Co., Ltd.), X-22-164A (Shin-Etsu Chemical Co., Ltd.), X-22-164B (Shin-Etsu Chemical Co., Ltd.), X-22-164C (Shin-Etsu Chemical Co., Ltd.), X-22-164E (Shin-Etsu Chemical Co., Ltd.), X-22-174DX (Shin-Etsu Chemical Co., Ltd.), etc.

[0167] The composition of the present invention can be suitably used as a cured coating film for imparting anti-fogging properties to a docking substrate by irradiating active energy rays after being coated on at least one side of a substrate formed of various materials. The cured coating film formed by the composition of the present invention can form a cured coating film and a cured product having anti-fogging properties that can be sustained for a long time and excellent abrasion resistance, anti-bleeding properties, adhesion, and resistance to moisture and heat. The cured coating film can withstand conditions under high temperature and humidity environments and conditions with many opportunities for contact with people and objects, and exerts excellent anti-fogging properties, so it can be suitably used as an anti-fogging coating film for automotive applications, display applications, and residential interior decoration, etc.

[0168] <Cured product / laminated body>

[0169] (Composition / Material)

[0170] The cured product of the present invention is obtained by irradiating the active energy ray-curable anti-fog coating composition of the present invention with active energy rays. When the cured product is in a film form, it is referred to as a cured coating film.

[0171] The laminated body of the present invention comprises at least a substrate and a cured coating film.

[0172] The substrate is not particularly limited and may be appropriately selected depending on the intended use. Examples thereof include plastic, glass, wood, metal, metal oxide, paper, silicon or modified silicon, and may be a substrate obtained by bonding different materials.

[0173] The shape of the substrate is also not particularly limited, and can be a flat plate, a sheet, or any shape corresponding to the purpose such as a curvature on the entire surface or a portion of a three-dimensional shape. In addition, the hardness and thickness of the substrate are also not limited.

[0174] As the plastic substrate, there is no particular limitation as long as it is formed by a resin, for example, the aforementioned thermosetting resin or thermoplastic resin can be used. As the substrate, a single resin or a substrate formed by blending multiple resins can be used, and it can also be a single layer or a laminated structure having more than two layers. In addition, these plastic substrates can also be fiber reinforced (FRP).

[0175] In addition, within the scope that does not hinder the effect of the present invention, the substrate may also contain known additives such as known antistatic agents, antifogging agents, anti-blocking agents, ultraviolet absorbers, antioxidants, pigments, organic fillers, inorganic fillers, light stabilizers, crystal nucleating agents, lubricants, etc.

[0176] The laminate of the present invention may further have a second substrate on the substrate and the cured coating. As the second substrate, the material is not particularly limited, and glass, wood, metal, metal oxide, plastic, paper, silicon or modified silicon, etc. can be cited, and it can also be a substrate obtained by joining different raw materials. The shape of the substrate is not particularly limited, and it can be a flat plate, a sheet, or any shape corresponding to the purpose such as a curvature on the entire surface or a part of a three-dimensional shape. In addition, the hardness, thickness, etc. of the substrate are also not limited.

[0177] The cured coating formed by the composition of the present invention has high adhesion to plastics or inorganic substances, so it can also be preferably used as an interlayer material of heterogeneous materials. It is particularly preferred that the substrate is plastic and the second substrate is an inorganic layer. As the inorganic layer, for example: quartz, sapphire, glass, optical film, ceramic material, inorganic oxide, vapor-deposited film (CVD, PVD, sputtering), magnetic film, reflective film, Ni, Cu, Cr, Fe, stainless steel and other metals, paper, SOG (spin-on glass (Spin On Glass)), SOC (spin-on carbon (Spin On Carbon)), polyester / polycarbonate / polyimide and other plastic layers, TFT array substrates, PDP electrode plates, ITO, metal and other conductive substrates, insulating substrates, silicon, silicon nitride, polysilicon, silicon oxide, amorphous silicon and other silicon substrates can be cited.

[0178] (Manufacturing method)

[0179] The laminate of the present invention can be obtained by applying the active energy ray-curable anti-fog coating composition of the present invention to at least one surface of a substrate formed of various materials and then irradiating the substrate with active energy rays.

[0180] The coating of the substrate can be carried out by a method of directly coating the composition on the substrate or directly forming the composition and then curing it.

[0181] In the case of direct coating, the coating method is not particularly limited, and examples thereof include spraying, spin coating, dipping, roll coating, doctor blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, and inkjet.

[0182] Alternatively, the cured coating of the composition of the present invention can be directly formed and laminated on a substrate formed of various materials. A semi-cured cured product can be laminated on a substrate and then fully cured, or a fully cured cured product can be laminated on a substrate. When the cured coating is directly formed, mold forming, embedding forming, vacuum forming, extrusion lamination forming, compression forming, etc. can be cited.

[0183] The composition of the present invention contains a compound having a polymerizable unsaturated group and can therefore be cured by irradiation with active energy rays.

[0184] The active energy rays include ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. Among these, ultraviolet rays (UV) are particularly preferred from the viewpoint of curability and convenience.

[0185] Here, when ultraviolet rays are used as active energy rays, for example, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, electrodeless lamps (fusion lamps), chemical lamps, black light lamps, mercury xenon lamps, short arc lamps, helium-cadmium lasers, argon lasers, sunlight, LED lamps, etc. are listed as devices for irradiating the ultraviolet rays as active energy rays. These are used to irradiate the applied or formed composition with ultraviolet rays of a wavelength of about 180 to 400 nm, thereby obtaining a cured coating film or a cured product. The irradiation amount of ultraviolet rays can be appropriately selected according to the type and amount of the photopolymerization initiator used.

[0186] The composition of the present invention may have a heating step before curing with active energy rays. By introducing the heating step, the solvent contained in the composition can be dried and the adhesion to the substrate can be improved.

[0187] As the device for performing heating, there can be mentioned: hot air dryer, IR heating type dryer, heating type hot plate, etc. When the substrate is plastic, the substrate adhesion can be improved by heating at 50°C to 110°C, preferably 70°C to 100°C. In addition, when the substrate is an inorganic substrate such as glass or steel plate, the substrate adhesion can be improved by heating at 80°C to 140°C, preferably 90°C to 130°C, and more preferably 100°C to 120°C.

[0188] (use)

[0189] The active energy ray-curable antifog coating composition of the present invention can form a cured coating film and a cured product having long-lasting antifogging properties and excellent abrasion resistance, exudation resistance, adhesion and moisture and heat resistance, and therefore can be suitably used in anti-scattering films for automobile glass, antifogging films for display cabinets, antifogging films for window glass, automobile headlights, displays for virtual reality (VR), surveillance cameras, mirrors for washing and dressing tables, sinks, bathtubs in bathrooms, walls of bathrooms, mirrors in bathrooms, etc. In addition, it can be suitably used in applications such as glasses, goggles, masks, various mirrors, various windows, partitions for infectious disease countermeasures, monitor covers, and sensor covers.

[0190] [Example]

[0191] The present invention will be described in more detail below using Examples and Comparative Examples, but the present invention is not limited to the following embodiments. In addition, "parts" and "%" in the present examples are based on mass unless otherwise specified.

[0192] (Synthesis Example 1: Synthesis of a Multifunctional (Meth)acrylate Compound (F-1) Having a Polyethylene Glycol Structure)

[0193] In a 3-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, 168.2 parts by mass of hexamethylene diisocyanate ("Desmodur H" manufactured by Covestro), 256 parts by mass of isobutyl acetate, 2.0 parts by mass of 2,6-di-tert-butyl-4-methylphenol, 0.2 parts by mass of methoxyhydroquinone, and 0.2 parts by mass of dibutyltin diacetate were added, and the temperature was raised to 70°C. Pentaerythritol triacrylate (trade name "ARONIX M-306" manufactured by Toagosei Co., Ltd., containing about 30% by mass of pentaerythritol tetraacrylate) (356.9 parts by mass) and polyethylene glycol ("PEG-1000" manufactured by Sanyo Chemical Industries, Ltd., number average molecular weight of about 1000) (496.5 parts by mass) were added in portions over 1 hour. After the addition, the reaction was carried out at 80°C until the isocyanate group showed a molecular weight of 2250 cm -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining a polyfunctional (meth)acrylate compound (F-1) having a polyethylene glycol structure and having a solid content of 80 wt % (containing about 10.5 wt % of pentaerythritol tetraacrylate in the solid content).

[0194] (Synthesis Example 2: Synthesis of a Multifunctional (Meth)acrylate Compound (F-2) Having a Polyethylene Glycol Structure)

[0195] A polyfunctional (meth)acrylate compound (F-2) having a polyethylene glycol structure (containing about 10% by mass of pentaerythritol tetraacrylate in the solid content) was obtained in the same manner as in Synthesis Example 1, except that 168.2 parts by mass of hexamethylene diisocyanate was replaced with 222.3 parts by mass of isophorone diisocyanate (trade name "IPDI", manufactured by Covestro Corporation).

[0196] (Synthesis Example 3: Synthesis of a Multifunctional (Meth) Acrylate Compound (F-3) Having a Polyethylene Glycol Structure)

[0197] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, 193.8 parts by mass of isocyanurate-type hexamethylene diisocyanate ("DURANATE N3300" manufactured by Asahi Chemical Industry Co., Ltd.), 109.4 parts by mass of isobutyl acetate, 0.9 parts by mass of 2,6-di-tert-butyl-4-methylphenol, 0.09 parts by mass of methoxyhydroquinone, and 0.09 parts by mass of dibutyltin diacetate were added, and the temperature was raised to 70°C. 77.4 parts by mass of 2-hydroxyethyl monoacrylate (trade name "HEA" manufactured by Osaka Organic Chemical Co., Ltd.) and 165.5 parts by mass of polyethylene glycol ("PEG-1000" manufactured by Sanyo Chemical Industry Co., Ltd., number average molecular weight of about 1000) were added in portions over a period of 1 hour. After the addition, the reaction was carried out at 80°C until the isocyanate group showed a molecular weight of 2250 cm -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of the mixture disappeared, thereby obtaining a polyfunctional (meth)acrylate compound (F-3) having a polyethylene glycol structure with a solid content of 80 wt %.

[0198] (Synthesis Example 4: Synthesis of a Multifunctional (Meth)acrylate Compound (F-4) Having a Polyethylene Glycol Structure)

[0199] The same procedure as in Synthesis Example 3 was followed except that 2-hydroxyethyl monoacrylate was replaced with 237.9 parts by mass of pentaerythritol triacrylate (trade name "ARONIX M-306" manufactured by Toagosei Co., Ltd., containing approximately 30% by mass of pentaerythritol tetraacrylate) to obtain a polyfunctional (meth)acrylate compound (F-4) having a polyethylene glycol structure and having a solid content of 80 wt% (containing approximately 12.0% by mass of pentaerythritol tetraacrylate in the solid content).

[0200] (Synthesis Example 5: Synthesis of a Multifunctional (Meth)acrylate Compound (F-5) Having a Polyethylene Glycol Structure)

[0201] A polyfunctional (meth)acrylate compound (F-5) having a polyethylene glycol structure and a solid content of 80 wt% was obtained in the same manner as in Synthesis Example 3, except that the polyethylene glycol was changed from 165.5 parts by mass of "PEG-1000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 1000) to 32.9 parts by mass of "PEG-200" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 200).

[0202] (Synthesis Example 6: Synthesis of a Multifunctional (Meth)acrylate Compound (F-6) Having a Polyethylene Glycol Structure)

[0203] A polyfunctional (meth)acrylate compound (F-6) having a polyethylene glycol structure and a solid content of 80 wt% was obtained in the same manner as in Synthesis Example 3, except that the polyethylene glycol was changed from 165.5 parts by mass of "PEG-1000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 1000) to 97.4 parts by mass of "PEG-600" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 600).

[0204] (Synthesis Example 7: Synthesis of a Multifunctional (Meth)acrylate Compound (F-7) Having a Polyethylene Glycol Structure)

[0205] A polyfunctional (meth)acrylate compound (F-7) having a polyethylene glycol structure and a solid content of 80 wt% was obtained in the same manner as in Synthesis Example 3, except that the polyethylene glycol was changed from 165.5 parts by mass of "PEG-1000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 1000) to 333.2 parts by mass of "PEG-2000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 2000).

[0206] (Synthesis Example 8: Synthesis of a Multifunctional (Meth) Acrylate Compound (F-8) Having a Polyethylene Glycol Structure)

[0207] A polyfunctional (meth)acrylate compound (F-8) having a polyethylene glycol structure and a solid content of 80 wt% was obtained in the same manner as in Synthesis Example 3, except that the polyethylene glycol was changed from 165.5 parts by mass of "PEG-1000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 1000) to 663.1 parts by mass of "PEG-4000" manufactured by Sanyo Chemical Industries, Ltd. (number average molecular weight of about 4000).

[0208] (Example 1)

[0209] As a solid content, 100 parts by mass of trimethylolpropane EO-modified triacrylate (modification number 3, EO average modification number 1, "Miramer M3130" manufactured by MIWON), 0.5 parts by mass of sodium alkylbenzene sulfonate (manufactured by Lion Specialty Chemicals, trade name "LIPON LH-200"), and 3 parts by mass of a photopolymerization initiator (1.5 parts by mass of Omnirad 2959 (manufactured by IGM), 1.5 parts by mass of Omnirad 819 (manufactured by IGM)) were added, and the mixture was uniformly mixed with propylene glycol monomethyl ether so that the solid content became 40 wt%, thereby preparing an active energy ray-curable anti-fog coating composition (1).

[0210] (Examples 2 to 83, Comparative Examples 1 to 2)

[0211] Active energy ray-curable anti-fog coating compositions (2) to (83) and (R1) to (R2) of each example were obtained in the same manner as in Example 1 except that the solid content compositions were changed to those shown in Tables 2 to 13.

[0212] [Preparation of evaluation sample (PET substrate)]

[0213] The active energy ray-curable anti-fog coating compositions (1) to (22), (62) to (81), (R1) to (R2) of each example were applied to a polyethylene terephthalate (PET) substrate (trade name "Lumirror UH-13" manufactured by Toray Industries, Ltd., thickness: 50 μm, area: 30 cm×15 cm) to give a film thickness of 5 μm, dried at 80° C. for 1 minute, and heated by a high-pressure mercury lamp at 180 mW / cm 2 、250mJ / cm 2 The PET substrate and the cured coating film were irradiated with ultraviolet rays under the conditions of , and the resulting laminate was used as an evaluation sample (PET substrate).

[0214] [Preparation of evaluation samples (glass substrates)]

[0215] The active energy ray-curable anti-fog coating composition (23) to (61) of each example was applied to a glass substrate (float glass manufactured by PALTEK, thickness: 3 mm, area: 15 cm×7 cm) in a film thickness of 5 μm, dried at 100° C. for 10 minutes, and then heated by a high-pressure mercury lamp at 200 mW / cm 2 、1000mJ / cm 2 The glass substrate and the cured coating film were irradiated with ultraviolet rays under the conditions of , and the obtained laminated body was used as an evaluation sample (glass substrate).

[0216] [Evaluation of initial anti-fogging properties]

[0217] The evaluation samples (PET substrate) and the evaluation samples (glass substrate) obtained above were set at a height of 2 cm from the water surface of a warm water bath maintained at 50°C so that the cured coating surface was facing downward, and the presence or absence of fogging when the coating film was continuously irradiated with steam from the warm water bath for 60 seconds was visually evaluated in the following three levels.

[0218] ◎: A water film is formed immediately after the steam is irradiated, but no fog is generated.

[0219] ○: Fogging was observed for a moment immediately after steam irradiation, but a water film was formed thereafter and no fogging occurred.

[0220] ×: A complete water film was not formed after steam irradiation, and fogging was observed.

[0221] [Evaluation of anti-fog durability]

[0222] After performing the above-mentioned [Evaluation of Initial Antifogging Properties], wipe off the water film with a wiping cloth and perform the [Evaluation of Initial Antifogging Properties] again. Measure the number of times until no water film is formed. For example, if no water film is formed at the end of performing the [Evaluation of Initial Antifogging Properties] three times in total, the number is 2. 2 or more is considered acceptable.

[0223] [Evaluation of bleed resistance after moisture and heat resistance test]

[0224] The evaluation samples (PET substrate) and evaluation samples (glass substrate) obtained above were left to stand at 50°C and 95% RH, and the presence or absence of bleeding was checked every 25 hours. The time taken until bleeding was confirmed was measured. The samples without bleeding at 25 hours were considered to be qualified.

[0225] [Evaluation of wear resistance]

[0226] Wipe with a clean cloth at 600g / cm 2 The cured coating surface of each evaluation sample was rubbed at 30 rpm with a load to perform an abrasion test. The number of reciprocating times when scratches were produced was recorded visually. The sample without scratches at the time of 100 times was considered qualified.

[0227] [Evaluation of Adhesion to Substrate]

[0228] A cutter was used to cut 10×10 grid-shaped slits with a width of 1 mm on the cured coating side of the evaluation sample (PET substrate) and the evaluation sample (glass substrate). Cellophane tape ("CT-24" manufactured by NICHIBAN) was attached to the grid-shaped portion and peeled off to observe whether there was peeling.

[0229] [Evaluation of substrate adhesion after moisture and heat resistance test]

[0230] The test piece was left to stand for 25 hours at 50°C and 95% RH, and the durability of the cured coating film against peeling was tested in accordance with JIS K 5600-5-6. If peeling occurred, the test was terminated, and if peeling did not occur, the same test was repeated after leaving the test piece to stand for 25 hours under the same conditions. This operation was repeated until peeling occurred, and the time taken until peeling occurred was measured.

[0231] Tables 1 to 13 show the compositions and evaluation results of the active energy ray-curable anti-fog coating compositions obtained in Examples 1 to 83 and the active energy ray-curable anti-fog coating compositions (1) to (83) and (R1) to (R2) obtained in Comparative Examples 1 to 2.

[0232] [Table 1]

[0233]

[0234] [Table 2]

[0235]

[0236] [Table 3]

[0237]

[0238] [Table 4]

[0239]

[0240] [Table 5]

[0241]

[0242] [Table 6]

[0243]

[0244] [Table 7]

[0245]

[0246] [Table 8]

[0247]

[0248] [Table 9]

[0249]

[0250] [Table 10]

[0251]

[0252] [Table 11]

[0253]

[0254] [Table 12]

[0255]

[0256] [Table 13]

[0257]

[0258] The abbreviations shown in Tables 1 to 13 represent the following compounds.

[0259] [(A) ingredient]

[0260] M3130: Trimethylolpropane EO-modified triacrylate (modification number 3, average EO modification number 1), trade name "Miramer M3130", manufactured by MIWON

[0261] M3160: Trimethylolpropane EO-modified triacrylate (modification number 6, average EO modification number 2), trade name "Miramer M3160", manufactured by MIWON

[0262] M3190: Trimethylolpropane EO-modified triacrylate (modification number 9, average EO modification number 3), trade name "Miramer M3190", manufactured by MIWON

[0263] M3150: Trimethylolpropane EO-modified triacrylate (modification number 15, average EO modification number 5), trade name "Miramer M3150", manufactured by MIWON

[0264] SR415:

[0265] A-DPH-6E: Ethoxylated dipentaerythritol polyacrylate (average EO modification number 1), trade name "NKESTER A-DPH-6E", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0266] A-DPH-12E: Ethoxylated dipentaerythritol polyacrylate (average EO modification number 2), trade name "NKESTER A-DPH-12E", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0267] A-DPH-24E: Ethoxylated dipentaerythritol polyacrylate (average EO modification number 4), trade name "NKESTER A-DPH-24E", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0268] DPEA42:

[0269] [(B) ingredient]

[0270] Alkylbenzene sulfonate: sodium alkylbenzene sulfonate, trade name "LIPON LH-200, manufactured by Lion Specialty Chemicals

[0271] OT-100: Dioctyl sodium sulfosuccinate, trade name "Aerosol OT-100", manufactured by Solvay

[0272] 12W-37: dodecyltrimethylammonium salt, trade name "Lipoquad 12-37W", solid content 37 parts by mass, manufactured by Lion Specialty Chemicals

[0273] TM-16: Cetyl trimethyl ammonium chloride, trade name "Lebon TM-16", solid content 30 parts by mass, manufactured by Sanyo Chemical Industries, Ltd.

[0274] TM-18: Stearyl trimethyl ammonium chloride, trade name "Lebon TM-18", solid content 70 parts by mass, manufactured by Sanyo Chemical Industries, Ltd.

[0275] 2C-75: Dicocoyl dimethyl ammonium chloride, trade name "Lipoquad 2C-75", solid content 75 parts by mass, manufactured by Lion Specialty Chemicals

[0276] DSV: Distearyl dimethyl ammonium chloride, trade name "CATION DSV", manufactured by Sanyo Chemical Industries

[0277] NL110: Polyoxyethylene alkyl ether (HLB: 14.4), trade name "NL-110", manufactured by Sanyo Chemical Industries, Ltd.

[0278] [(C) ingredient]

[0279] AA: Acrylic acid

[0280] ·HOA-MS: 2-Acryloyloxyethyl succinate, trade name "HOA-MS", manufactured by Kyoeisha Chemical

[0281] ACB-3: 2-Acryloyloxyethyl hexahydrophthalate, trade name "NK ESTER ACB-3", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0282] [(D) ingredient]

[0283] KBM-503: 3-methacryloxypropyltrimethoxysilane, trade name "KBM-503", manufactured by Shin-Etsu Chemical Co., Ltd.

[0284] KBM-5103: 3-Acryloxypropyltrimethoxysilane, trade name "KBM-5103", manufactured by Shin-Etsu Chemical Co., Ltd.

[0285] ·KBM-5803: 8-methacryloyloxyoctyltrimethoxysilane, trade name "KBM-5803", manufactured by Shin-Etsu Chemical Co., Ltd.

[0286] [(E) ingredient]

[0287] TEMPTA: trimethylolpropane triacrylate, trade name "TEMPTA", manufactured by DAICEL-ALLNEX

[0288] PETA: Pentaerythritol tetraacrylate, trade name "ARONIX M-450", manufactured by Toagosei Co., Ltd.

[0289] DPHA: Dipentaerythritol hexaacrylate, trade name "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.

[0290] [(F)INGREDIENT]

[0291] (F-1) to (F-8) synthesized in Synthesis Examples 1 to 8 were used.

[0292] [Photopolymerization initiator]

[0293] A mixture containing 50% of 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (trade name "Omnirad 2959", manufactured by IGM) and 50% of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", manufactured by IGM)

[0294] [Solvent]

[0295] Propylene glycol monomethyl ether

[0296] It was confirmed that the cured coating film of the active energy ray-curable antifog coating composition of the present invention can form a cured coating film having long-term antifogging properties and excellent abrasion resistance, bleed resistance, adhesion and moisture and heat resistance.

[0297] On the other hand, in Comparative Example 1 using a compound having an average EO modification number exceeding 5 as component (A), the anti-bleeding and abrasion resistance were significantly reduced. Furthermore, it was confirmed that in Comparative Example 2 not containing component (A), the anti-fogging property, anti-fogging persistence, anti-bleeding and substrate adhesion were poor.

Claims

1. An active energy ray-curable anti-fog coating composition comprising a radical polymerizable compound (A) having any structure of the following formulae (1) to (3) and a water-soluble surfactant (B), In formula (1), n ​​is an integer of 0 to 10, and (2+n) Xs are independently a (meth)acryloyl group modified with ethylene oxide represented by CH2=CR-CO(OC2H4)y-, a (meth)acryloyl group represented by CH2=CR-CO-, or a hydrogen atom, wherein R in the CH2=CR-CO(OC2H4)y- represents a hydrogen atom or a methyl group, and y represents the number of modifications based on ethylene oxide; wherein R in the CH2=CR-CO- represents a hydrogen atom or a methyl group; and at least one of the plurality of Xs represents a (meth)acryloyl group modified with ethylene oxide; and the average number of modifications of ethylene oxide per (meth)acryloyl group in the compound is 1 to 5; In formula (2), n is an integer of 0 to 4, and (4+2n) Xs are independently a (meth)acryloyl group modified with ethylene oxide represented by CH2=CR-CO(OC2H4)y-, a (meth)acryloyl group represented by CH2=CR-CO-, or a hydrogen atom, wherein R in the CH2=CR-CO(OC2H4)y- represents a hydrogen atom or a methyl group, and y represents the number of modifications based on ethylene oxide; wherein R in the CH2=CR-CO- represents a hydrogen atom or a methyl group; and at least one of the plurality of Xs represents a (meth)acryloyl group modified with ethylene oxide; and the average number of modifications of ethylene oxide per (meth)acryloyl group of the compound is 1 to 5; In formula (3), n is an integer from 0 to 3, and (3+n) Xs are independently a (meth)acryloyl group modified with ethylene oxide represented by CH2=CR-CO(OC2H4)y-, a (meth)acryloyl group represented by CH2=CR-CO-, or a hydrogen atom, wherein R in CH2=CR-CO(OC2H4)y- represents a hydrogen atom or a methyl group, and y represents the number of modifications based on ethylene oxide; wherein R in the CH2=CR-CO- represents a hydrogen atom or a methyl group; and at least one of the plurality of Xs represents a (meth)acryloyl group modified with ethylene oxide; and the average number of modifications of ethylene oxide per (meth)acryloyl group of the compound is 1 to 5. 2 . The active energy ray-curable anti-fog coating composition according to claim 1 , further comprising a compound (C) having a carboxyl group and a (meth)acryloyl group and a compound (D) having an alkoxysilyl group and a (meth)acryloyl group. 3 . The active energy ray-curable anti-fog coating composition according to claim 1 , further comprising a polyfunctional (meth)acrylate (E) which is not modified with ethylene oxide. 4 . The active energy ray-curable anti-fog coating composition according to claim 1 , comprising a polyfunctional (meth)acrylate (F) having a polyethylene glycol structure. 5 . A cured product, which is a cured product of the active energy ray-curable resin composition according to claim 1 . 6 . A laminate having a cured coating film on at least one side of a plastic substrate, wherein the cured coating film comprises the cured product according to claim 5 . 7 . A cured product, which is a cured product of the active energy ray-curable resin composition according to claim 2 . 8 . A laminate having a cured coating film on at least one surface of a glass substrate, wherein the cured coating film comprises the cured product according to claim 7 .

Citation Information

Patent Citations

  • Ultraviolet-curing type antifogging composition

    JP2005239832A

  • Active energy ray-curable antifogging composition and cured product

    JP2019210396A